PERBANDINGAN ANTARA POLA KUMAN TRAKEA DAN STOMA DENGAN ANGKA KEJADIAN INFEKSI STOMA TRAKEA DI RSMH PALEMBANG - Kusmawijaya, Vitta; Yanti, Lisa Apri (RSUP Dr. Kariadi, 2023)
BACKGROUND: Tracheostomy is a procedure to incise or make a hole in the trachea. The use of tracheal cannula leads to direct exposure of pathogens to the respiratory tract. It is necessary to identify bacterial pattern in an attempt to overcome tracheal stoma infections in order to prevent further complications. OBJECTIVE : This study is to compare bacterial pattern in trachea and tracheal stoma on the incidence of tracheal stoma infection. METHODS: Observational research with a cross-sectional design. Medical record data on 60 subjects who underwent tracheal and tracheal stoma swabs and culture examination from November 2020 to October 2021 were collected. Bivariate analysis using Fischer exact test and Chi-square categorical comparative test. RESULTS: Sixty subjects obtained 13 species of bacteria, all identified as gram-negative bacteria. Most of the bacterial sequences and analysis of bacterial pattern were Pseudomonas aeruginosa(p>0.05), Klebsiela pneumonia(p>0.05), Escherichia coli (p>0.05) and Serratia marcescen(p>0.05) on the incidence of tracheal stoma infection. CONCLUSION: There is no difference in the bacterial pattern of the trachea and tracheal stoma on the incidence of tracheal stoma infection.